Comportamente şi strategii manageriale în organizaţiile non-guvernamentale - Boboc, Ion (Calitatea Vieții, 2006)
In our applicative research we took the typology realized by American researchers R.E. Miles & C.C. Snow regarding organizational strategies of American NGO’s, and than we applied it, in June 2005, at 25 Romanian NGO’s, founded after 1990. Our results confirm the hypothesis of the two american researchers, regarding different types of NGO’s around the world.